New York: The Animated City. (December 2013) - Pallant, Chris
Abstract : The urban landscape of New York City is one that is familiar to many, but, through the medium of animation, this familiarity has been consistently challenged. Often metamorphic, and always meticulously constructed, animated imagery encourages reflective thinking. Focusing on the themes of construction, destruction, and interactivity, this article seeks to cast critical light upon the animated double life that New York City has lived through the following moving image texts: Disney's Fantasia 2000 (1999), Patrick Jean's computer-generated short Pixels (2009), and Rockstar Games' open-world blockbuster Grand Theft Auto IV (2008).